Perubahan Siklus Menstruasi Pada Akseptor KB Pengguna Kontrasepsi Suntik Tiga Bulan di Puskesmas Kecamatan Ciracas - Adrian Goenawan; Andreas Evangelius Messakh; Johnny Johnny; Erma Mexcorry Sumbayak (Universitas Pahlawan Tuanku Tambusai, 2026)
The contraceptive method that many women choose is the injectable contraceptive method. However, injectable contraceptives also have many side effects such as changes in blood pressure, menstrual disorders, changes in sexual desire, changes in body weight. The aim of the study was to determine the relationship between the use of 3-month injectable contraceptives and the menstrual cycle in mothers at the Ciracas District Health Center. The research design used is an analytic descriptive design with a cross sectional approach. The sampling technique is by using consecutive sampling method with a total sample of 105 respondents. The results of the study using the chi square statistical test obtained a value of P = 0.04 <0.05. In conclusion, there is a significant relationship between the use of 3-month injectable contraceptives and the menstrual cycle in women at the Ciracas District Health Center.